Adapting to Environmental Change: Assessing the Vulnerability of Inuvialuit Communities to Infrastructure Risks Associated with Climate Change - Pearce, T (2005)
There is growing concern among Canadian Inuit about the impacts on the environment from global changes such as climate change. To date, the focus on this subject has been oriented on biophysical changes and impacts in the environment and little attention has been given to the potential vulnerability of community infrastructure. Research on vulnerability and adaptation to climate change has most often taken the form of impact studies with the purpose of estimating the physical impacts of climate change (Parry and Carter, 1998; Fankhauser et al., 1999). Adaptations were then considered as an end cost of climate change. However, it is now becoming increasingly recognized that initiatives to identify adaptation needs and to improve adaptive capacity start with an assessment of vulnerability of the system of interest (Ford and Smit, 2004). This draws on insights from political ecology scholarship which shows that access to resources, equity, livelihoods and the political and socio-economic conditions are important considerations in the assessment of adaptive capacity, and therefore vulnerability (Blaikie et al., 1994; Adger and Kelly, 1999; Bohle, 2001; Smit and Pilifosova, 2001; O’Brien et al., 2004).